BIOFILM FORMATION OF METHICILLIN AND VANCOMYCIN RESISTANT STAPHYLOCOCCUS SPECIES ISOLATED FROM CELLULAR PHONES - Pattnaik, Swati; Mishra, Shatabdi; Mohapatra, Swati; Rath, Chandi Charan; Maity, Sudipta; Samantaray, Deviprasad (International Journal of Pharmacy and Pharmaceutical Sciences, 2018)
Objective: The goal of the study was to explore the occurrence of methicillin and vancomycin-resistant Staphylococcus species from cellular phones and preventive measures to avoid contamination. Methods: The issues addressed in this investigation are i) Isolation of bacteria from 70 cellular phones through swab culture method ii) Characterization of the isolates by standard biochemical test iii) Antibiogram pattern study of the isolates iv) Molecular identification of the selected isolate through 16s rDNA sequencing v) Virulence study through biofilm assay vi) Susceptibility of the isolates against commonly used disinfectants and essential oils through disc diffusion. Results: All 70 different cellular phone used in this study harbored 120 isolates of bacteria. Of which, we recorded high incidence of Gram-positive cocci (51.6%) and 22 isolates were identified as Staphylococcus species. Three isolates (52N6, 53N9 and 53N6) were resistant to both methicillin and vancomycin, in addition, showed resistance against several other antibiotics. The strain 53N6 that exhibited multidrug resistance was further identified as Staphylococcus sp. strain CPC53N6 through 16s rDNA sequencing with NCBI accession no. KX858346. Virulence activity of the isolate was observed by its biofilm forming capacity as revealed from SEM imaging and the biofilms were composed of aggregated cocci and fibriform extracellular matrix. All the Staphylococcus isolates, including CPC53N6, were sensitive to disinfectants like dettol and cinnamon (Cinnamon zeylanicum) oil indicating their use as preventive measures. Conclusion: Thus, the methicillin and vancomycin-resistant Staphylococcus species of cellular phones can be decontaminated through cinnamon oil to minimize further transmission.